2008
DOI: 10.1007/s00264-008-0587-y
|View full text |Cite
|
Sign up to set email alerts
|

Supracondylar periprosthetic femoral fractures following total knee arthroplasty: treatment with a retrograde intramedullary nail

Abstract: Total knee replacement surgery is occasionally complicated by a supracondylar periprosthetic fracture, and this presents a challenging problem in an often frail population. Multiple nonoperative and operative treatments have been described which have the aim of restoring the patient to their pre-injury status. This study retrospectively reviews the results of the largest series to date of 14 such fractures treated by retrograde intramedullary supracondylar nailing and is supportive of its continued use with go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 24 publications
0
29
0
Order By: Relevance
“…14,23,54,58 -60 In one comparative clinical study between the LISS and the retrograde nail, 11% of the intramedullary implants failed. 36 Chettiar et al 61 retrospectively reviewed the results of 14 supracondylar periprosthetic fractures treated by retrograde intramedullary nailing and found good functional outcomes, low complications rates, and 100% fracture union. In another study, one LISS (20%) with a flexion deformity of 16°f ailed.…”
Section: Discussionmentioning
confidence: 98%
“…14,23,54,58 -60 In one comparative clinical study between the LISS and the retrograde nail, 11% of the intramedullary implants failed. 36 Chettiar et al 61 retrospectively reviewed the results of 14 supracondylar periprosthetic fractures treated by retrograde intramedullary nailing and found good functional outcomes, low complications rates, and 100% fracture union. In another study, one LISS (20%) with a flexion deformity of 16°f ailed.…”
Section: Discussionmentioning
confidence: 98%
“…They concluded that the retrograde nail should be considered the treatment of choice for type I and II SFF above TKA. Weber et al, 14 Chettiar et al, 17 and Chen et al 16 retrospectively reviewed patients with SFF above TKA and reported limited complications and good functional and radiological outcomes. However, El-Kawy et al 8 considered the high incidence of TKA malalignment in an elderly population with intra-articular SFF (without TKA) a contraindication for retrograde nailing.…”
Section: Discussionmentioning
confidence: 97%
“…Angular correction and additional stability can be achieved bx placing blocking screws in the distal fragment (Stedtfeld et al, 2004). In a retrospective study, 14 supracondylar periprosthetic fractures obtained good functional outcomes, a low complication rate and 100% fracture unions (Chettiar et al, 2009). …”
Section: Minimally Invasive Osteosynthesis With Internal Fixators Andmentioning
confidence: 99%
“…Numerous studies (Chettiar et al, 2009;Gliatis et al, 2005;Henry, 1995;Murrell & Nunley, 1995;Platzer et al, 2010;Rolston et al, 1995;Smith et al, 1996) recommend nailing in the posterior cruciate ligament retaining femoral component with an open box. The supracondylar nail preserves the fracture haematoma, does not require extensive soft-tissue stripping, and provides fair stability to the fracture (Figgie et al, 1990;Gardner et al, 2004;Gliatis et al, 2005;Kolb et al, 2008;Mittlmeier & Beck 2005;Stedtfeld et al, 2004).…”
Section: Minimally Invasive Osteosynthesis With Internal Fixators Andmentioning
confidence: 99%
See 1 more Smart Citation